2010
DOI: 10.1002/art.27529
|View full text |Cite
|
Sign up to set email alerts
|

Lesional and nonlesional skin from patients with untreated juvenile dermatomyositis displays increased numbers of mast cells and mature plasmacytoid dendritic cells

Abstract: Objective To investigate the distribution of mast cells and dendritic cell (DC) subsets in paired muscle and skin (lesional/nonlesional) from untreated children with juvenile dermatomyositis (DM). Methods Muscle and skin biopsy samples (4 skin biopsy samples with active rash) from 7 patients with probable/definite juvenile DM were compared with muscle and skin samples from 10 healthy pediatric controls. Mast cell distribution and number were assessed by toluidine blue staining and analyzed by Student’s t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…As in SLE, autoantigens of apoptotic origin provide the immunogenic stimulus for the initiation of pathogenic responses (78). RNA-containing immune complexes can activate pDCs in salivary glands and enhance the production of IFN-, while IFN- itself can upregulate the expression of ISGs in the target organs (87,88). Early studies clearly identified an IFN signature in salivary glands from patients with pSS; IRF7, IRF8, and IRF9 were significantly upregulated (91,92).…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…As in SLE, autoantigens of apoptotic origin provide the immunogenic stimulus for the initiation of pathogenic responses (78). RNA-containing immune complexes can activate pDCs in salivary glands and enhance the production of IFN-, while IFN- itself can upregulate the expression of ISGs in the target organs (87,88). Early studies clearly identified an IFN signature in salivary glands from patients with pSS; IRF7, IRF8, and IRF9 were significantly upregulated (91,92).…”
Section: Sjögren's Syndromementioning
confidence: 99%
“…Specific use of topical corticosteroids or topical immunomodulators (tacrolimus, pimecrolimus) can be helpful for limited rashes when disease activity is confined to the skin and not amenable to systemic therapy, or for more severe rashes, including scalp involvement 103 . Antihistamines and moisturizers are helpful for treating associated pruritis, given the presence of dermal mast cells in the skin of JDM patients 106 . Hydroxychloroquine, which inhibits Toll-like receptor activation, has anecdotally been helpful as an adjunctive agent and has been shown to improve cutaneous and renal disease activity and prevent disease damage in lupus 107 .…”
Section: Treatment Approaches For Juvenile Dermatomyositismentioning
confidence: 99%
“…Indeed, pDCs are present in both muscle and skin of DM patients [16, 26, 27, 35, 46•, 47, 48]. The presence of mature pDCs has been shown in perivascular and perimysial infiltrates in muscle biopsies from DM and JDM patients [16,26,47,48]. Mature pDCs in DM muscle also express CD83 (a maturation marker) as well as chemokines CCL21, CCL19, and CXCL12, all of which are important for dendritic cell migration into regional lymph nodes [47].…”
Section: Interferon-inducible Transcripts and Proteins In Dermatomyosmentioning
confidence: 98%